Breaking the Maxims of Grice’s Cooperative Principle in Literary Texts - Okunienė, Eiginta (Kalbotyra, 2002)
The article analyses how breaking the maxims of Grice’s Cooperative Principle is exploited in literary texts. The distinction is drawn between two types of maxim non-observance: flouting, i.e. overt breaking of maxims with an intention that the hearer recognises that, and violation, i.e. covert breaking of maxims when the speaker breaks them secretly or not realising he is doing that. By flouting, different implicatures and figurative meanings are created that enhance expressiveness and thus are commonly met in literary texts. Violation of maxims, which usually creates misunderstanding and hinders communication, is more rarely met in literary texts, and the author explores how humour, ambiguity, nonsense and other linguistic fun is created by violating the four maxims of Grice’s cooperative principle in Lewis Carroll’s works.